Seborrheic dermatitis: comparative effectiveness of standard and intermittent external therapy - Evgeny A. Vasiliev-Stupalsky (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Background. The chronic and recurrent nature of seborrheic dermatitis, its wide prevalence and multifactorial etiopathogenesis require a comparison of the effectiveness of different treatment strategies. Aim. In a randomized controlled trial to evaluate the effectiveness of standard and intermittent therapy with topical corticosteroids and activated zinc pyrithione (Skin-cap cream) in reducing the severity of clinical manifestations, the duration of remission of the disease, and compliance with treatment. Methods. The effectiveness of external therapy in patients with seborrheic dermatitis of the face and scalp was studied. All the examined patients had at least two episodes of exacerbation per year. Doctor's prescription Mometasone furoate cream 0.1% 1 time/day externally for 14 days, activated zinc pyrithione (Skin-cap cream) 2 times/day externally for 14 days, further 1 time a day 2 times a week for 14 days. Results. There was a comparable clinical effectiveness of antiinflammatory therapy in the short term with more stable results of intermittent therapy with the use of (Skin-cap cream) in the long term. Conclusions. Usage of activated zinc pyrithione (Skin-cap cream) according to the intermittent scheme in the treatment of seborrheic dermatitis of the face with the transition to the scalp is associated with long-term results. Safety of medicine allows to use it pro re nata by patients, e.g., in case of increased stress levels, diet incompliance, with no risks of adverse events, specific to topical corticosteroids, those increases treatment compliance.